PEMANFAATAN ARSIP REKAM MEDIS DALAM ANALISIS POLA PELAYANAN KESEHATAN PASIEN RAWAT INAP DI RUMAH SAKIT TAHUN 2025 - Muhammad Aditya Rachman; Muhammad Habibullah Aminy; Lale Ajeng Khalifatun Wardani; Slamet Mardiyanto Rahayu (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2026)
Medical record archives play a crucial role in supporting healthcare services, particularly in providing reliable data for evaluation and decision-making. This study aims to analyze inpatient healthcare service patterns based on medical record archives in hospitals in 2023. The research employed a descriptive method with a retrospective approach using archival document analysis. The results indicate that medical record archives provide comprehensive information regarding patient conditions, treatment patterns, and healthcare services. From an archival perspective, properly managed records improve data accessibility, accuracy, and accountability. However, inconsistencies in documentation and incomplete records were still found, which may affect data quality. This study highlights the importance of strengthening medical record management systems to support effective healthcare services and evidence-based decision-making.